Cooperation under punishment: Imperfect information destroys it and centralizing punishment does not help - Sven Fischer; Kristoffel Grechenig; Nicolas Meier (Max Planck Institute for Research on Collective Goods, 2013)
We run several experiments which allow us to compare cooperation under perfect and imperfect information and under a centralized and decentralized punishment regime. We find that (1) centralization by itself does not improve cooperation and welfare compared to an informal, peer-to-peer punishment regime and (2) centralized punishment is equally sensitive to noise as decentralized punishment, that is, it leads to significantly lower cooperation and welfare (total pro ts). Our results shed critical light on the widespread conjecture that the centralization of punishment institutions is welfare increasing in itself.
Keywords: C92; K42; H42; D03; 330; public goods; cooperation; centralized punishment; imperfect information; decentralized punishment; peer to peer punishment